Antimicrobial stewardship programmes in healthcare facilities in Lagos State, Nigeria: a needs assessment. (June 2021) - Chukwu, Emelda E.; Oshun, Philip O.; Osuolale, Kazeem A.; Chuka-Ebene, Vivian O.; Salako, Abideen; Idigbe, Ifeoma E.; Oladele, David; Audu, Rosemary A.; Ogunsola, Folasade T.
Highlights: No formal ASP in place in 80% of healthcare facilities, and only six facilities had an AMS team. No dedicated financial support in any facility and limited IT resources especially in primary and secondary facilities. Only two facilities (8%) perform prospective audit and feedback and 28% monitor adherence to guidelines. No private healthcare facility produced a cumulative antimicrobial susceptibility or AMS annual report for previous year. Tracking was generally poor in healthcare facilities with ASPs, with only monitoring of adherence to treatment guidelines. ABSTRACT: Objectives: Optimising antibiotic use in healthcare settings through antimicrobial stewardship programmes (ASPs) is critical to effectively treat infections, protect patients from harms caused by unnecessary antibiotic use, and combat antimicrobial resistance. This needs assessment was designed to provide the current status of ASPs in healthcare facilities in Lagos State and identify gaps for future interventions. Methods: A descriptive cross-sectional survey was conducted using a self-administered questionnaire to ascertain the extent and nature of ongoing ASPs among selected healthcare facilities and identify gaps for future interventional studies. Results: Of 32 questionnaires distributed, 25 (78%) were completed and returned from three tertiary, six secondary, eleven primary and five private healthcare facilities. The mean years of practice of respondents was 13.96 ± 7.8 years (2–31 years). Six facilities (24%) had a team responsible for ASP operating at varying degrees of capacity, while five (20%) had a formal ASP. All six facilities with an antimicrobial stewardship (AMS) team had a medical doctor as the team lead, and 5 (20%) also had a pharmacist involved in implementation efforts. Routine pre-authorisation for specific antibiotic was performed in six facilities (24%), four of which monitor pre-authorisation interventions. Only two facilities (8%) performed prospective audit and feedback for specific antibiotic agents. Private healthcare facilities were more likely to have information technology (IT) capability to support the needs of AMS activities. Conclusion: This study revealed minimal ASP activities in healthcare facilities in Lagos State and highlighted possibilities of leveraging on available IT resources for a co-ordinated AMS strategy.